Spanish education journals and their citation sources: exploring the CiteScore 2021 - Estrada Molina, Odiel; Aguaded, Ignacio; Repiso, Rafael (Revista General de Información y Documentación, 2023)
There are several research that analyze the evolution of Spanish education journals in the Web of Science and Scopus databases. However, there are no studies that analyze the origin of their citations. For this reason, the objective was to explore citation origin of Spanish education journals through the analysis of the CiteScore 2021. For this, a descriptive and retrospective study was carried out, applying a procedure that included the analysis of these CiteScore of the Spanish journals of education. The population are journals indexed in Scopus (1369) under the subcategory of education (Social Science -education-), and the sample are the Spanish journals (70). Matrices were designed to analyze the quantitative data using the Microsoft Excel spreadsheet, the Pakej v. 5.15, the VOSviewer v. 1.6.18 and, the power-user plugin for citation analysis and data rendering. The results highlight the excellent job done by the editors of the Spanish education journals. The analysis of the main citation sources of Spanish education journals reveals two aspects to assess: the origin of publications whose indexation in Scopus is far from «education» and the influence of conference proceedings.